Feeding Behaviour, Performance and Nutrient Utilization of Different Growing Goat Breeds Fed Creep Feed - Astuti, Dewi Apri; Permana, sep Tata; Stevani, Rori; Ramadhania, Tariza; Khotijah, Lilis; Fassah, Dilla Mareistia (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
This study was aimed to evaluate feeding behaviour, performance and nutrient utilization of goats fed different form of creep feed. Twelve local growing goats (average age 5 months, BW 20.0±1.57 kg), consisting of six Etawah crossbred and six Senduro goats were included in the study. The study was conducted in a factorial completely randomized block design of 2x2. The first factor was type of creep feed form (mash and pellet), and the second factor was type of goat breed (Etawah crossbred and Senduro). The ration consisted of 70% creep feed containing BSF (black soldier fly) meal and oil plus 30% elephant grass. The variables observed were feeding behaviour, nutrient consumption, digestibility, blood metabolites, and performance. Results showed that there was no interaction between the creep feed forms and the goat breeds in any of the variables. The form of creep feed had a significant effect (p<0.05) on prehension and mastication, but it had no significant effect on nutrient consumption and digestibility. The goat breeds had a significant effect (p<0.05) on crude fiber digestibility, being higher in Etawah crossbreds. Performance and blood metabolites were same in all treatments, except for the feed efficiency which was higher in Senduro goats than Etawahs. In conclusion, giving creep feed as pellet form resulted in a lower prehension and higher mastication, whereas mash type feed required higher prehension and lower mastication in both goat breeds.